Global discord Global discord - Tucker, Paul (Princeton University Press Princeton, 2022)
"Can the international economic and legal system possibly survive today's fractured geopolitics? Cooperation between states and peoples, and so myriad supranational organizations, depend on peaceful coexistence and some limited trust. But the West and China, and maybe other authoritarian states, are gripped by intense long-term jealousies that back when Britain and France were commercial and military superpowers took more than a century to resolve. No longer silos, today economic, environmental, health and human rights policies are entangled with security issues, and almost any instrument - from the dollar to cyber commerce - can be weaponized given globalization's connectivity and over-dependencies. Drawing on civilizational histories, economics, political and legal philosophy, as well as long policymaking experience, Paul Tucker offers a new account of international relations that avoids prioritizing just one of power, interests, or values. Rejecting intellectual traditions harking back to Hobbes, Kant, and Grotius, he instead deploys David Hume, the late-20th century philosopher Bernard Williams, and modern mechanism-design economists to emphasize, in a political realism that does not jettison morality, how incentives must be aligned with values for institutions to endure. The connecting tissue is legitimacy, heralding a world of concentric circles where we cooperate more deeply with those with whom we share more, and fear less. The book's principles for general international law and organizations can help constitutional democracies navigate power politics without losing themselves. Tucker applies them with rare practical know-how to the international monetary order, the trade and investment regimes, and the financial system"-- Provided by publisher.
Includes bibliography and index
Keywords: International order